Validation of DNA Damage Progression with Days after Single Exposure of Sublethal Dosage of Electron Beam Radiation - Madhu L N, Suchetha Kumari N, Vijay R (Journal of Applied Pharmaceutical Science)
The aim of this study was to asses the DNA damage progression with days after single exposure of 6Gy electron beam radiation (EBR). Molecular DNA damage in lymphocytes of mice was assessed using alkaline comet assay and in bone marrow cells by micronucleus assay. In comet assay %DNA in tail, Comet length, Olive Tail Moment (OTM) served as a measure of DNA damage and in micronucleus test, frequency of micronucleus formation in bone marrow cells was measured to evaluate the DNA damage. The experiment was performed by taking 24 healthy Swiss albino mice with body weight 30+5g. The animals were grouped into four. Group1 served as control, Group 2, 3 and 4 were irradiated by 6Gy EBR. Animals of Group 2, 3 and 4 were sacrificed on 5th, 10th and 15th day post irradiation respectively. The comet assay procedure was carried out for all these groups by using lymphocytes separated from EDTA treated blood. The micronucleus test was performed in bone marrow cells (PCE-Poly chromatic erythrocytes, NCE-normochromatic erythrocytes). The slides prepared for this were scored for the measure of DNA damage. The results showed all comet parameter were significantly (P
Keywords: Electron Beam Radiation, DNA damage, Micronucleus, Comet.